2021
DOI: 10.3390/medicina58010031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Hypertrophic Cardiomyopathy

Abstract: Background and Objectives: Hypertrophic cardiomyopathy (HCM) depends on the primary impairment of sarcomeres, but it can also be associated with secondary alterations in the heart related to oxidative stress. The present study aimed to examine oxidative-antioxidant disturbances in patients with HCM compared with control individuals. Materials and Methods: We enrolled 52 consecutive HCM patients and 97 controls without HCM. The groups were matched for age, body mass index, and sex. Peripheral blood was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Advanced stages of non-obstructive HCM can be and are mostly associated with increased myocardial fibrosis, microvascular ischemia, and abnormal cardiac function [8]. Novel findings suggest that HCM is associated with an increased oxidative stress and that markers of oxidative stress could even be used to identify patients with HCM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced stages of non-obstructive HCM can be and are mostly associated with increased myocardial fibrosis, microvascular ischemia, and abnormal cardiac function [8]. Novel findings suggest that HCM is associated with an increased oxidative stress and that markers of oxidative stress could even be used to identify patients with HCM [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, in a pioneering study Dimitrow et al reported the occurrence of increased oxidative stress in patients with HCM evidenced by increased serum levels of 8-isoprostaglandin F(2alpha), which was the highest in the subgroup of HCM patients with LVOT obstruction [23]. More recently, Szygula-Jurkiewicz et al evaluated the total oxidative-antioxidant balance in patients with HCM and showed that patients with HCM had prooxidative changes with predictive value as compared to controls [24].…”
Section: Discussionmentioning
confidence: 99%
“…Increased cytosolic ADP increases the oxidation of two metabolic enzymes (NADH and NADPH), which decreases the capacity to attenuate mitochondrial reactive oxygen species (ROS) levels, as NADPH is necessary to detoxify ROS ( 30 ). Increased ROS subsequently impairs mitochondrial activation and contributes to HCM development ( 33 ). Additionally, reduced phosphocreatine (PCr)/ATP ratios in HCM, both with and without hypertrophy, indicate cardiac energetic impairments are present at an early stage of HCM ( 34 ).…”
Section: Metabolic Changes In Inherited Cardiomyopathiesmentioning
confidence: 99%